Information as an asset – Today's Board Agenda: The value of rediscovering gold. (June 2019) - Ward, Sandra; Carter, Denise
In today's fast moving environment, organizations either thrive or fail depending on how they manage information. Information is a critical and strategic organizational asset and must be harnessed as a business asset. This requires action and leadership at Board level. In 1995, a pivotal report, the Hawley report, argued this case forcibly and presented an agenda for Board action developed through discussion among 30 UK private and public sector organizations working within a KPMG IMPACT programme. Actions to ensure that Board operation was underpinned by sufficient and valid information were accompanied by recommended measures to ensure information assets were well and legally managed and deployed to advantage at every level of operations. A successor report has just been published by the Chartered Institute of Information Professionals, KPMG, CIO Connect and IK SpringBoard supported by the Network for Information and Knowledge Exchange. It reinforces the responsibilities of Boards in leading their organization's information vision, policy, strategy and governance. This article explains why senior leadership is so vital as the fourth industrial age is followed by the fifth and the power of information is transformed through artificial intelligence and Interconnection.